Effects of supplementing mare diets with marine-derived n-3 fatty acids on serum, follicular fluid and follicular dynamics during the estrous cycle - Schmidt, Mikki (Kansas State University, 2010)
The objective of this study was to evaluate the reproductive effects of supplementing normally cycling mares with marine-derived omega-3 (n-3) fatty acids during the estrous cycle. Fifteen mares were assigned to a control diet (CONT, n=7) or a fish oil supplemented diet (FO, n=8) containing eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). The FO mares received 18.48 g EPA/10.08 g DHA/mare/d. At the start of the trial, mares were synchronized using a progesterone and estradiol protocol. Following synchronization, mares were monitored with transrectal ultrasonography throughout the second estrous cycle. Ovarian activity, ovulation, and presence of a corpus luteum were noted. Mares were ultrasounded throughout the third estrous cycle until a 35 mm follicle was detected. Upon detection of the 35 mm follicle, hCG was administered. Within 16 hr, transvaginal ultrasound-guided follicular aspiration (TUGA) was performed on the preovulatory follicle, signifying the end of the trial. Follicular fluid was analyzed for fatty acid and hormone concentrations. Serum fatty acids were measured every 2 wk and serum hormone concentrations were analyzed during the second estrous cycle at 5 d to 1 d prior to ovulation, at ovulation, and 3 and 5 d post-ovulation. Samples were also collected prior to hCG administration and on aspiration day for hormone analysis. Serum estradiol-17β, progesterone, luteinizing hormone (LH), and insulin-like growth factor 1 (IGF-1) were measured. Fish oil supplementation increased (P < 0.01) arachidonic acid (ARA), EPA, docosapentaenoic acid (DPA), and DHA in mare serum and increased (P<0.01) EPA, DPA, and DHA in follicular fluid. No overall treatment effect was found on serum hormone concentrations during the second estrous cycle, but a decrease (P<0.05) in IGF-1 was noted in the FO group on aspiration day. Concentrations of IGF-1 were also lower (P<0.05) in follicular fluid in the FO group compared to controls. No other follicular fluid differences were observed. Supplementation resulted in a smaller diameter follicle (P<0.05, 38.0 ± 0.47 mm) on aspiration day than the CONT group (39.5 ± 0.5 mm). Dietary n-3 fatty acids modify mare serum and follicular fluid fatty acid profiles, with supplementation of EPA and DHA decreasing serum and follicular IGF-1 concentrations.
Keywords: Equine; Reproduction; Polyunsaturated fatty acids; Mare; Omega-3 fatty acids; Fish oil; Agriculture, Animal Culture and Nutrition (0475)